The Impact OF Human Resources Management Strategies on the Strategic Agility: A Field Study in large and medium Yemeni manufacturing Sector - Barahma, Maged Mohammed; ALi, Kalsom Binti; Nashief, Mohammad; Al-Awlaqi, Mohammed Ali (Journal of Social Sciences (COES&RJ-JSS), 2019)
Under the dynamic capabilities view of the firm the main purpose of this paper is to provide an analytical model of knowledge gaps on the direct impact of HRM strategy on strategic agility, as well as the direct impact of HRM strategies which is represented in HR Strategy, Training Strategy Human Resources Development Strategy, Human Resources Compensation Strategy, Career Planning Strategy) on strategic agility. To achieve this, the main study survey, which was distributed to managers and their deputies in the large and medium Yemeni industrial companies (227), was based on the simple random sample of 554 companies, this work uses structural equations modeling technique, in order to test and validate the research model and hypotheses posited. The results indicated that there is a direct impact of human resources management strategies on strategic agility, as well as the direct impact of the career planning strategy and the strategy of training and developing human resources on strategic agility. In contrast, there is no direct impact of HR strategy, human resources performance assessment, and human resources compensation on the strategic agility of the Yemeni large and medium manufacturing sector (current study sample).